Identifikasi Akuifer Dangkal di Pulau Terdepan NKRI dengan Menggunakan Metode Geolistrik 2D: Studi Kasus Pulau Laut, Kab. Natuna - Pryambodo, Dino Gunawan; Pihantono, Joko; Troa, Reiner Arief; Triarso, Eko (BRIN Publishing, 2016)
The need for fresh water to support community activities in the field of fisheries on the frontier island is necessary because this location has minimal condition to the source of fresh water. Geophysical research with 2D geoelectrical methods conducted to identify the aquifers in the area of Pulau Laut, Natuna Regency as the frontier island of United Country of Republic Indonesia (NKRI). In field, measurement is using six 2D geoelectric lines with Wenner configuration and 160 m cable stretching to obtain 26.9 m sub-surface depth penetration. Resistivity data in Pulau Laut used to identify the aquifer presence in research area. Aquifers are located on varies depth near the surface with a depth of 2.5 – 13 m in north line, PDAM line, and Air Paying line; 12 – 26.9 m in Kadur line, Air Bunga line, and Air Paying line. Resistivity value for each aquifer varies for each line. They are ranging from 0.651 – 14 Ωm. Lithologies, composing the aquifer, are sandstone unit in Kadur, Air Bunga, Talaga Tasik, and Air Paying lines; silstone in PDAM line; and limestone in the north line.